Nutritional Status and Anemia in Islamic Boarding School Adolescent in Kediri City East Java Indonesia - Sodik, Muhammad Ali; Yudhana, Amarin; Dwianggimawati, Mayta Sari (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
Anemia is one of the major health problems in the world that is often overlooked in both developing and developed countries. Toddlers, pregnant women and adolescents are a high risk group of anemia. Although anemia has been known as a community nutrition problem for many years, progress in reducing its prevalence is still considered low. Even in some countries found an increase in the prevalence of anemia in adult women. The purpose of this study was to determine the relationship of nutritional status with the incidence of anemia in adolescent girls in Islamic boarding schools in Kediri City.The design of this study was an observational study with a cross sectional approach. By using sistematic random sampling technique, a sample of 294 respondents was obtained. The independent variables studied was nutritional. The dependent variable studied was anemia status in adolescent girls. The instrument used was a questionnaire, the data were analyzed using simple poisson regression test with a robust variance estimator at a significant level of 5%. The prevalence ratio and 95% confidence interval were presented. From the results of the study, it was found that prevalence of anemia among adolescent girls was 29,93%. There was a relationship between nutritional status and anemia among adolescent girls (PR = 3.280, 95% CI = 2.330-4.616). Islamic boarding schools are expected to facilitate and strive to improve adolescent reproductive health, especially in preventing anemia by holding a forum such as PIK KRR (Information Center for Adolescent Reproductive Health Counseling) or other containers that can answer student questions related to reproductive health